Recriminalizing Blasphemy? Human Rights Anlysis of Religious Freedom Limits and Doctrinal Reform of Offense Law - Rainrat Budi Prasetya; Z. Zainuddin; M. Mursyid (Manunggal Halim Jaya, 2026)
This study examines the contemporary debate on the recriminalization of blasphemy through a human rights perspective, with particular emphasis on the limits of religious freedom and the doctrinal foundations of modern criminal law. The research aims to evaluate whether blasphemy can be justified as a legitimate criminal offense within the framework of international human rights norms and to propose a coherent doctrinal reform aligned with harm-based principles. Employing a normative legal research method, the study utilizes statutory and conceptual approaches by analyzing relevant legislation, international human rights instruments, and legal doctrines concerning freedom of religion and expression. The data are analyzed using a descriptive-prescriptive technique, which not only explains existing legal norms but also formulates normative recommendations. The findings reveal that blasphemy laws, as traditionally constructed, suffer from significant doctrinal deficiencies, particularly in relation to the principles of legality, necessity, and proportionality. These laws often rely on vague and subjective interpretations of offense, leading to inconsistent enforcement and potential violations of fundamental rights. The study further finds that the conflation of subjective religious offense with objective legal harm results in the overextension of criminal law and disproportionately severe sanctions. Consequently, blasphemy fails to meet the threshold of a legitimate criminal offense unless it is narrowly defined as conduct that incites violence, discrimination, or hostility. The study concludes by proposing a doctrinal reform that shifts the focus from protecting religious doctrines to safeguarding individuals, thereby ensuring a more balanced and rights-oriented legal framework.